2014
DOI: 10.1590/1982-0224-20130201
|View full text |Cite
|
Sign up to set email alerts
|

The effect of structural enrichment in hatchery tanks on the morphology of two neotropical fish species

Abstract: Reared fish differ from wild fish in several aspects, including morphology, because they are adapted to captive conditions that are totally different from natural conditions. To minimize the influence of the hatchery environment on the morphology of fish, the use of environmental enrichment through the incorporation of natural designs in captivity, has been proposed. In the present study, we performed the physical structuring of fish farming tanks to verify the enrichment effect on the morphology of two specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(45 reference statements)
1
4
1
Order By: Relevance
“…They attribute the lower feeding efficiency to the macrophytes, that obstruct light, restrict predators in their movement and increase the chances for mobile invertebrates to escape from an attack. In another recent study, we found that artificial macrophytes hamper the development of curimba, decreasing the condition factor of individuals (Saraiva and Pompeu, 2014). However, in the present study, the condition factor of curimba in the tanks treated with macrophytes was not significantly affected, but this may be a result of the higher mortality and consequent lower density in these tanks.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…They attribute the lower feeding efficiency to the macrophytes, that obstruct light, restrict predators in their movement and increase the chances for mobile invertebrates to escape from an attack. In another recent study, we found that artificial macrophytes hamper the development of curimba, decreasing the condition factor of individuals (Saraiva and Pompeu, 2014). However, in the present study, the condition factor of curimba in the tanks treated with macrophytes was not significantly affected, but this may be a result of the higher mortality and consequent lower density in these tanks.…”
Section: Discussioncontrasting
confidence: 87%
“…In the present study, by comparing tanks with and without piapara we were able to detect an effect of this species on the morphology of curimba. By comparing tanks without structures to those with different structure types, we could also demonstrate the structural enrichment effect, in the same way as in a previous study (Saraiva and Pompeu, 2014). Since the same pattern of results was found in both studies we can certify, despite the lack of replications, that the changes in fish morphology were a result of the treatment itself and not of a possible tank effect.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, changes in behavioural responses to structural enrichment depend on ontogenetic life‐stages of reared fish 52 . Furthermore, Saraiva and Pompeu 53 demonstrated that structural EE (submerged logs and artificial aquatic plants) can induce morphological differentiation in two Neotropical species ( Prochilodus lineatus , Brycon orbignyanus ) through phenotypic plasticity, potentially generating phenotypes more adapted to exploiting a complex environment. In addition, the use of nets in hatchery and nursery tanks is known to be widely used in gilthead seabream ( Sparus aurata ) and European seabass ( Dicentrarchus labrax ) farms (Arechavala‐Lopez P. pers .…”
Section: Environmental Enrichment Strategiesmentioning
confidence: 99%
“…(2010) have found significant differences in body and head shapes of 3-spine stickleback Gasterosteus aculeatus , depending on whether fish were reared in an environment with just gravel or in an environment enriched with large stones and artificial plants. Similarly, according to Saraiva and Pompeu (2014) , structural enrichment has a strong effect on some morphological traits such as a smaller size of the head and enlarged fins in the Neotropical fish species Brycon orbignyanus (suggesting a differentiation that facilitates manoeuvrability). Although changes are much more likely to occur at early developmental stages than in later ones ( Meuthen et al.…”
mentioning
confidence: 99%